More than Mrs. Robinson: citizenship schools in Lowcountry South Carolina and Savannah, Georgia, 1957-1970 - Russell, Clare (2010)
The first “citizenship school” (a literacy class that taught adults to read and write in order that they could register to vote) was established by Highlander Folk School of Monteagle, Tennessee on Johns Island, South Carolina in 1957. Within three years, the schools were extended across the neighboring Sea Islands, to mainland Charleston and to Savannah, Georgia. In 1961, after Highlander faced legal challenges to its future, it transferred the schools to the fledgling Southern Christian Leadership Conference (SCLC), who extended the program across the South. Historians have made far-reaching claims for the successes and benefits of the schools. For example, they claim that they recruited inexperienced but committed people and raised them to the status of community leaders; that they encouraged civic cooperation and political activism and formed the “foundation on which the civil rights movement” was built and they argue that the schools were an unprecedented opportunity for women to develop as activists and as leaders. Yet, they base these claims on certain myths about the schools: that the first teacher Bernice Robinson was an inexperienced and uneducated teacher, that her class was a blueprint for similar ones and that Highlander bequeathed its educational philosophy to the SCLC program. They make claims about female participation without analyzing the gender composition of classes. This dissertation challenges these assumptions by comparing and contrasting programs established in Lowcountry South Carolina and in Savannah. It argues that not only was Robinson more skilled and better educated than historians have assumed, but that she was not typical of early teachers. On the Sea Islands, teachers tended to be established community leaders, such as ministers. In Savannah, they were young college students involved in direct action spaces. It analyzes the gender composition of classes, the gendered nature of the spaces in which classes were taught, and the different models of black masculinity (based on class, location and generational identity) that the schools emulated. It argues that while Robinson may have been influenced by Highlander philosophy, the educational materials used in classes indicate that the schools drew more on Septima Clark’s experience of African American educational history than on Highlander’s ethos of education for social change. Local variations, including gender, class, location and age, also shaped teaching curricula. Finally, it examines the reasons for the schools’ failure in the mid to late 1960s. Far from fading away because they became superfluous after the 1965 Voting Rights Act, the schools failed both because of factors at the administrative level (disorganization, mismanagement and gender conflict) and at the local (conflict between generations and local groups.)